IMPLEMENTASI PRINSIP KERJA 5S PADA BAGIAN PABRIKASI I UNTUK MENINGKATKAN EFISIENSI WAKTU PRODUKSI - Hartono, Gunawarman; Suntantyo, Fanni Abdillah (Industrial and Systems Engineering Assessment Journal (INASEA), 2008)
The bridge construction industry has a unique characteristics compared to other industrial companies, namely its production system should be able to meet increasing demands and very high fluctuations. Limited space in the production line and increasing operational costs have made the management of PT BMI obtaining a more appropriate management strategy for its production system. In this research, the author attempts to implement the 5S principle in production management. This study aims to implement and reveal the effectiveness of production time from the implementation of 5S principle in the Fabrication 1 division. The study is also conducted by formulating the actual problem, followed by literature review and direct observation in the field for calculation of requirements to achieve full implementation of the 5S principle. This study recommends the company to implement the 5S principle to other divisions, due to proven increase in efficiency.